Multifunctional, stable and low-cost lipopeptide biosurfactant produced by Enterobacter cloacae UCP 1597 (Research, Society and Development, 2022)
Caatinga of Pernambuco is an area with a potential richness of microorganisms that produce biosurfactants, which are considered good candidates to replace synthetic surfactants in industrial applications due to their functional stability and low toxicity. In this context, current study aimed to investigate the biosurfactant production by the bacterium Enterobacter cloacae UCP 1597, isolated from the Caatinga soil. First fermentation was carried out in Erlenmeyer flasks containing 100 ml of medium, according to a 2³ full-factorial design (FFD). The results showed higher reduction in surface tension (28.3 mN/m) in condition 2 of the FFD, where dispersion of 38.46 cm2 of burnt motor oil was also verified. Then, a second fermentation was performed in Fernbach flasks, containing 2 L of selected medium, confirming reduction in surface and interfacial tension to 30.5 and 2.3 mN/m, respectively, as well as excellent emulsifying properties. The critical micellar dilution (CMD) of the crude biosurfactant was determined (70%) and its use in phytotoxicity assay verified the absence of toxicity for cabbage seeds. The biomolecule showed a high yield (13.69 g/L) after extraction with ethyl acetate and anionic and lipopeptide nature. The stability in acid pH, high temperature and salinity, showed an acid-resistant, thermostable, and halotolerant biocompound. Thus, this lipopeptide was shown to be a multifunctional biosurfactant, since it not only has excellent surface-active properties, but it is also a good emulsifier, dispersant, and potent agent to germination of cabbage seeds. Hence, is suggested its promising application in industrial activities or environmental processes under adverse conditions.